2012
DOI: 10.2169/internalmedicine.51.8636
|View full text |Cite
|
Sign up to set email alerts
|

Total and HMW Adiponectin is Independently Associated with B-type Natriuretic Peptide and Anemia in Chronic Hemodialysis Patients

Abstract: Objective A number of vasculo-protective roles have been reported for adiponectin. In contrast, higher, rather than lower, plasma adiponectin levels are associated with an increased risk of cardiovascular disease and mortality in patients undergoing hemodialysis (HD). The mechanisms by which high adiponectin levels are associated with adverse outcome are unclear. Methods This study measured the level of total and high molecular weight (HMW) adiponectins in 70 patients with HD patients (age: 65.2±8.6 years, man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…levels in HD patients (Abe et al, 2012;El-Shafey & Shalan, 2014). BMI, waist circumference, body fat mass, and TG and fasting glucose levels were negatively correlated with fasting serum adiponectin levels among peritoneal dialysis patients in another study (C. H. Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…levels in HD patients (Abe et al, 2012;El-Shafey & Shalan, 2014). BMI, waist circumference, body fat mass, and TG and fasting glucose levels were negatively correlated with fasting serum adiponectin levels among peritoneal dialysis patients in another study (C. H. Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 88%
“…Metabolic syndromeis a cluster of metabolic abnormalities consisting of central obesity, insulin resistance, hyperglycemia, dyslipidemia, and hypertension (Alberti, Zimmet, & Shaw, 2006). Previous research has shown that plasma adiponectin levels were inversely related to BMI and TG and glucose levels in HD patients (Abe et al, 2012; El-Shafey & Shalan, 2014). BMI, waist circumference, body fat mass, and TG and fasting glucose levels were negatively correlated with fasting serum adiponectin levels among peritoneal dialysis patients in another study (C.…”
Section: Discussionmentioning
confidence: 91%
“…Adiponectin is a cytokine released by adipocytes that has been shown in basic studies to suppress hematopoiesis [26]. Other studies also showed a negative correlation between elevated adiponectin and both low hemoglobin and low triglycerides in patients with coronary artery disease [27], chronic kidney disease [28] and diabetic patients [29,30]. Moreover, adiponectin levels were found to be higher in diabetic women than men [30].…”
Section: Discussionmentioning
confidence: 96%